Simulation and experimental verification of ambient neutron doses in a pencil beam scanning proton therapy room as a function of treatment plan parameters - Van Hoey, Olivier; Stolarczyk, Liliana; Lillhök, Jan; Eliasson, Linda; Mojzeszek, Natalia; Liszka, Malgorzata; Alkhiat, Ali; Mares, Vladimir; Trompier, François; Trinkl, Sebastian; Martínez-Rovira, Immaculada; Romero-Expósito, Maite; et al. (Frontiers in Oncology, 2022)
Out-of-field patient doses in proton therapy are dominated by neutrons. Currently, they are not taken into account by treatment planning systems. There is an increasing need to include out-of-field doses in the dose calculation, especially when treating children, pregnant patients and patients with implants. In response to this demand, this work presents the first steps towards a tool for the prediction of out-of-field neutron doses in pencil beam scanning proton therapy facilities. As a first step, a general Monte Carlo radiation transport model for simulation of out-of-field neutron doses was setup and successfully verified by comparison of simulated and measured ambient neutron dose equivalent and neutron fluence energy spectra around a solid water phantom irradiated with a variation of different treatment plan parameters. Simulations with the verified model enabled a detailed study of the variation of the neutron ambient dose equivalent with field size, range, modulation width, use of range shifter and position inside the treatment room. For future work it is planned to use this verified model to simulate out-of-field neutron doses inside the phantom and to verify the simulation results by comparison with previous in-phantom measurement campaigns. Eventually, these verified simulations will be used to build up a library and corresponding tool to allow assessment of out-of-field neutron doses at pencil beam scanning proton therapy facilities.